PERLINDUNGAN HUKUM PADA PASIEN TERHADAP MALPRAKTEK DOKTER - Evander Reland Butar Butar; Suteki Suteki (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2018)
Patient is any person who consulted a physician profession regarding his or herhealth problems to get healed from his illness. Patient is king in health service. Inorder to get the case, a patient will be checked for health by a doctor who has licensedthe practice. In article 44 of Law no. 29 Year 2004 on the practice of Medical states"Doctors and dentists in conducting medical practice must follow the standard ofmedical services". In carrying out the duties of the profession, the doctor has a noblereason that is trying to maintain the condition of the patient's body to stay healthy andtry as much as possible to make healthy body of the patient, but the health services ofa doctor performed to the patient not as successful and satisfactory, but there at timesthe business fails, organ rigidity, even death to the patient.This research is a legal research using normative juridical approach. AccordingSoerjono Soekanto normative juridical research is a study of legal principles. Thenormative approach is made in discussing the Legal Protection of Patients onMedical Malpractice According to Law No. 29 of 2004 on Practice Doctors in orderto achieve significant and relevant results. The data data used is primary dataderived from the authorized Institution Institutions such as the National Commissionfor Child Protection which is then supported with secondary data that is relevantliterature to strengthen the analysis of this study.The results of research and discussion show that the legal protection for patientsagainst malpractice doctors can be seen in the Law or Code of ethics profession ofmedicine. Furthermore for the legal effort that can be taken by the patient is themediation path, if the mediation is not resolved, then the patient can sue thepharmacist in court and outside court.